Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm suppose to translate the following sets into $A$, $B$, and $C$ using $\cap$, $\cup$, and $-$.

$$F=\{ x : x \in A \text{ and } (x \in B \implies x \in C)\}$$

My first attempt was: $$F= A \cap (B \cap C)$$.

But my worry is about everything within the parentheses. I'm aware that $$B \cap C=\{x : x \in B\} \text{ and } \{x : x \in C\}.$$ This is not an implication.

share|improve this question
    
Can you just write $B\Rightarrow C$? E.g. using the logic formulas for $b\to c$ via $\wedge$ and $\vee$? –  Ilya Jan 16 '13 at 9:50
    
I'm not sure I follow. Would $B \rightarrow C$ require an and or or? –  emka Jan 16 '13 at 9:58
    
Well, what is the definition of $B\rightarrow C$ that you have? –  Ilya Jan 16 '13 at 9:58

2 Answers 2

up vote 1 down vote accepted

Edit: I've rewritten my answer because I think I aimed it at a different level when I didn't really need to.


Consider the definition of $F$: $$F = \left\{ x : x \in A \text{ and if } x \in B \text{ then } x \in C \right\}$$ If we're to have $x \in F$ then we must certainly have $x \in A$, since otherwise the condition isn't satisfied. So we know that $F \subseteq A$.

This means that we obtain $F$ by throwing out some elements of $A$ $-$ namely, those elements which don't satisfy the condition.

Which elements do we throw out? Precisely those which are in $B$ but not in $C$. Since if an element is in $B$ but not $C$ then $x \in B \to x \in C$ isn't satisfied (and these are the only elements for which this condition isn't satisfied).

So we need to throw out $B - C$. That is, $F = A - (B - C)$.

share|improve this answer
    
Should it be $A \cap (B-C)$? I ask this because in order for $x \in F$ it has to be in both $A$ and $B-C$. At least that is how I read it. –  emka Jan 16 '13 at 10:42
1  
@emka: No. If $x \in B-C$ then $x \in B$ but $x \not \in C$; but we need $x \in B \to x \in C$, so if $x \in F$ and $x \in B$, then $x$ has to lie in $C$! And indeed, we don't even need $x \in B$ for the condition to hold: we could have $x \in C$ and $x \not \in B$, for example (as long as $x \in A$). –  Clive Newstead Jan 16 '13 at 11:41
    
More concretely, let $A$ be the set of integers, $B$ be the set of even integers and $C$ be the set of multiples of $3$. Then a 'thing' is in $F$ if it is an integer and whenever it is even it is also a multiple of $3$... so $F$ is the set consisting of all the odd integers and those even integers which are multiples of $3$ (i.e. multiples of $6$). This is the same as taking the set of all integers and throwing out the even integers which are not multiples of $3$. –  Clive Newstead Jan 16 '13 at 11:44

$p\implies q$ is equivalent to $\neg p\vee q$, so $$x\in A\wedge(x\in B \implies x\in C)$$ is equivalent to $$x\in A\wedge(x\notin B \vee x\in C)$$ Also we have that $\neg\neg p\equiv p$, so we can write it as $$x\in A\wedge \neg(\neg(x\notin B\vee x\in C))$$ and by De Morgan's laws $$x\in A\wedge\neg(x\in B \wedge x\notin C)$$ Finally $(x\in A\wedge x\notin B)\equiv x\in(A\cap B)$, and applying it twice we get $$x\in A\smallsetminus(B\smallsetminus C)$$hence $F=A\smallsetminus(B\smallsetminus C)$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.